The effector function of mucosal associated invariant T cells alters with aging and is regulated by RORγt - Yang, Zhi; Luo, Banxin; Li, Minhuan; He, Ziyun; Ren, Chuanfu; Chen, Xin; Kang, Xing; Chen, Hong; Xu, En; Guan, Wenxian; Xia, Xuefeng (Frontiers in Immunology, 2024)
IntroductionMucosal-associated invariant T (MAIT) cells are a predominant subset of innate-like T cells in humans, characterized by diverse gene expression profiles and functional capabilities. However, the factors influencing the transcriptomes and effector functions of MAIT cells, particularly at mucosal barriers, remain largely unclear.MethodsIn this study, we employed single-cell RNA sequencing (scRNA-seq) and functional assays to investigate the transcriptomic and functional characteristics of intestinal MAIT cells in mouse models during aging. We also extended scRNA-seq analysis to human intestinal MAIT cells to compare their gene expression patterns with those observed in aged mice.ResultsOur findings demonstrated that the transcriptomes and functional capabilities of intestinal MAIT cells shifted from MAIT17 to MAIT1 profiles with aging in mouse models, with notable changes in the production of cytotoxic molecules. Further scRNA-seq analysis of human intestinal MAIT cells revealed a segregation into MAIT1 and MAIT17 subsets, displaying gene expression patterns that mirrored those seen in aged mouse models. The transcription factor RORγt was expressed in both MAIT1 and MAIT17 cells, acting to repress IFNγ production while promoting IL17 expression. Moreover, reduced expression of RORC and Il17A was correlated with poorer survival outcomes in colorectal cancer patients.DiscussionThese results suggest that aging induces a functional shift between MAIT1 and MAIT17 cells, which may be influenced by transcriptional regulators like RORγt. The observed alterations in MAIT cell activity could potentially impact disease prognosis, particularly in colorectal cancer. This study provides new insights into the dynamics of MAIT cell responses at mucosal barriers, highlighting possible therapeutic targets for modulating MAIT cell functions in aging and disease.